Trace Elements and Microbiological Analysis - Mansi Ankolekar; Freny Karjodkar (Wolters Kluwer Medknow Publications, 2005)
"Theories born of bare experience and meager knowledge led to discoveries demanding and exacting martyrdom, even death, before the truth unfolded itself for us and future generations." In an era where humans are predisposed to infection easily, a lot of importance is given to food quality standards. Gutkha per say is not included in consumable items by authorities defining standards for food quality. But gutkha / pan masala is chewed frequently, which can be gauged by the fact that the Indian Market for pan masala is worth more than two hundred million rupees. This very fact, underlined the need to evaluate the hygiene status of these products. Oral Submucous Fibrosis is known and established to be precancerous. Hence, it is important to evaluate the precancerous potential of areca nut and it's products and also it's role in fibrosis.